Cochlear Aperture Abnormalities - Tahir, E.; Ozgen, B.; Sennaroǧlu, L. (Springer International Publishing, 2022)
Cochlear aperture (CA) (bony cochlear nerve canal) carries the cochlear nerve between the internal auditory canal (IAC) and modiolus. Atresia or stenosis of the CA has been found to correlate with cochlear nerve (CN) deficiency. CA can be considered as "normal" if the mid-portion or mid-modiolar width of the CA is ≥1.5 mm. CA is defined as "stenotic" when its mid-modiolar width is <1.5 mm. When the CA is not visible and it is occluded by bony tissue, CA is accepted as "atretic." These abnormalities may be "isolated" or may present concomitantly with another IEMs. If these abnormalities do not accompany any other IEMs regarding the bony labyrinth they can be named as "isolated cochlear aperture atresia" and "isolated cochlear aperture stenosis." In these situations, cochlear nerve is usually deficient. Since an atretic or stenotic CA is usually seen together with a narrow or absent internal auditory canal (IAC), the developmental relationship between IAC, CA, and CN will be discussed in this chapter. According to the most widely accepted hypothesis a deficient CN cannot release adequate amount of growth factors which result in interruption of development of bony structures. As the developing IAC requires the presence of a normal CN, it is likely that the CA also requires a similar neural stimulus for normal development. The recommended radiological evaluation method for the measurement of CA is high-resolution temporal bone computed tomography (HRCT) of the temporal bone. The measurement of CA should be performed at mid-modiolar section in axial sections. After identification of the fundus of the IAC, the length of the CA should be measured by drawing a perpendicular line from the base of the modiolus to the fundus of the IAC. Then, the mid-portion width of the CA can be measured. In this chapter, radiological evaluation is demonstrated by illustrations and CT images. Audiological findings in atretic or stenotic CA reveal CN deficiency. If there is no other cochlear malformation, otoacoustic emissions may be detected in the absence of auditory brainstem response (ABR). Thus, during neonatal screening these cases may be misdiagnosed as "auditory neuropathy." A narrow or atretic cochlear aperture is generally associated with sensorineural hearing loss necessitating cochlear implantation (CI) or auditory brainstem implantation (ABI). Children with CN deficiency tend to have poor outcomes after CI. Therefore, decision making process between CI and auditory brainstem implantation (ABI) becomes more complicated and radiological findings must be supported by audiological data. Based on these facts, measurement of CA diameter may help predict cochlear nerve status and CI outcomes. © Springer Nature Switzerland AG 2022. All rights reserved.
Keywords: Bony Cochlear Nerve Canal; Cochlear Aperture; Cochlear Nerve Deficiency; Internal Auditory Canal; Unilateral Sensorineural Hearing Loss